2017
DOI: 10.2217/pme-2016-0104
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Clinical Adoption of Next-Generation Sequencing: A Policy Delphi Panel’S Solutions

Abstract: Aim Identify solutions to the most important policy barriers to the clinical adoption of next-generation sequencing. Materials & methods Four-round modified policy Delphi with a multistakeholder panel of 48 experts. The panel deliberated policy solutions to (previously reported) challenges deemed most important to address. Results The group advocated using consensus panels to promote consistency in payer policies and to standardize test reporting, and favored making genomic data-sharing a condition of regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…2,[7][8][9][10][11][12][13][14] Despite widespread adoption of some guidelines, such as those of the American College of Medical Genetics and Genomics (ACMG), 7 studies investigating patients' and nonspecialists' satisfaction and perceptions find that existing reports leave substantial room for improvement. 4,[15][16][17] Genomic reports are especially challenging due to lack of standardization 18,19 and the complexity and uncertainty of the information involved. 20 There have been attempts to make the interpretation of laboratory reports clearer to nonspecialist clinicians, 16,[21][22][23][24][25] but far fewer to make them clearer to patients.…”
Section: Introductionmentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13][14] Despite widespread adoption of some guidelines, such as those of the American College of Medical Genetics and Genomics (ACMG), 7 studies investigating patients' and nonspecialists' satisfaction and perceptions find that existing reports leave substantial room for improvement. 4,[15][16][17] Genomic reports are especially challenging due to lack of standardization 18,19 and the complexity and uncertainty of the information involved. 20 There have been attempts to make the interpretation of laboratory reports clearer to nonspecialist clinicians, 16,[21][22][23][24][25] but far fewer to make them clearer to patients.…”
Section: Introductionmentioning
confidence: 99%
“…When CMA results are not informative, exome and genome sequencing (ES/GS) have been added to the clinical testing options for many individuals affected with a genetic disease 39 . However, several challenges regarding the high cost of instrumentation, bioinformatics core/expertise, and lack of streamlined analysis and reporting tools limit the implementation and reporting of ES/GS in a standardized manner [39][40] . Multiple studies have also revealed the utility of OGM complementing sequencing technologies in resolving rare undiagnosed diseases such as atypical teratoid rhabdoid tumors (ATRT) and inherited retinal diseases 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The lessons we summarize in this report provide practical guidance not only for researchers who conducting their own cost analyses, but also for scientists and policymakers who are interpreting the findings from other work. Aggregated estimates of the costs of sequencing, such as those provided by the National Human Genome Research Institute [54], may be inappropriate if they don’t account for differences in testing choices that may be influenced by the clinical context and patient characteristics, as well as regulatory requirements from oversight organizations such as the FDA [55]. We were able to develop valid estimates of WGS costs in our study by implementing a work-intensive microcosting approach, but more importantly, researchers of the cost impact of NGS tests will need to be careful to incorporate the full variability of approaches that may be appropriate to their clinical contexts and patient populations.…”
Section: Discussionmentioning
confidence: 99%